Human capital, trade liberalization, and income risk - Maloney, William F., 1959- 1959- (The World Bank, 2007)
Using data from Mexico, the authors study empirically the link between trade policy and individual income risk and the extent to which this varies across workers of different human capital (education) levels. They use longitudinal income data on workers to estimate time-varying individual income risk parameters in different manufacturing sectors in Mexico between 1987 and 1998, a period in which the Mexican economy experienced substantial changes in trade policy. In a second step, they use the variations in trade policy across different sectors and over time to estimate the link between trade policy and income risk for workers of varying education levels. The authors' findings are as follows. The level of openness of an economy is not found to be related to income risk for workers of any type. Furthermore, changes in trade policy (that is, trade policy reforms) are not found to have any effect on the risk to income faced by workers with either low or high levels of human capital. But workers with intermediate levels of human capital are found to experience a statistically and economically significant increase in income risk immediately following liberalization of trade. The findings thus point to an interesting non-monotonicity in the interaction between human capital, income risk and trade policy changes